ZnO Q-dots as a potent therapeutic nanomedicine for in vitro cytotoxicity evaluation of mouth KB44, breast MCF7, colon HT29 and HeLa cancer cell lines, mouse ear swelling tests in vivo and its side effects using the animal model. (5th November 2018) - Fakhroueian, Zahra; Vahabpour, Rouhollah; Assmar, Mehdi; Massiha, Alireza; Zahedi, Afshin; Esmaeilzadeh, Pegah; Katouzian, Fatemeh; Rezaei, Sara; Keyhanvar, Peyman; Mozafari Dehshiri, Alireza
Abstract: Nanoformulations derived from fine porous ZnO quantum dot nanoparticles (QD NPs) can offer strong potential medical applications; especially in cancer therapy. ZnO QD NPs was synthesized by sol–gel hydrothermal process, fast cold quenching and further smart surface functionalization methods to obtain ultrasmall size (1–4 nm) NPs. ZnO nanopolymer, a wetting agent, PEG co-solvent and water/ oil emulsion stabilizer were considered in our nanofluid formulation. The resulting nanofluid was characterized by SEM, FTIR, photoluminescence, band gap energy, zeta potential and UV–Vis spectroscopy. The cytotoxic effects on the growth of four cancer cell lines were evaluated by MTT assay. The IC50 (µg/ml) values of 30, 41, 40 and 35 for KB44, MCF-7, HT29 and HeLa cells, respectively, after 48 h of nanoformulation treatment suggested the cytotoxic effect of this nanoformulation on these cell lines in a concentration-dependent manner ( p < .05). ZnO nanofluid destroyed cancer cell lines more efficiently than the normal HFF-2 (IC50 = 105 µg/ml). The reduction in cell viability in response to ZnO nanofluid treatment induced apoptosis in the cultured cells. Skin sensitization test plus antibacterial activity were also measured. Side effect tests on 70 white mice in vivo resulted in only 3–4 abnormal situations in hepatic tissue section possibly due to the idiosyncratic drug reactions. Graphical Abstract: